THE INFLUENCE OF ENVIRONMENTAL FACTORS IN THE DEVELOPMENT OF ATOPIC DERMATITIS DISEASE IN CHILDREN - Salomova F. I.; Sadullaeva K. A.; Sadirova M. K. (Journals Park Publishing, 2024)
The prevalence of atopic dermatitis (AD) is increasing worldwide. Literature data suggest that the incidence of AD in developing countries is gradually approaching that of developed countries, where AD affects 20% of the pediatric population. Such an increase, which is associated with a significant variation in prevalence in different countries, emphasizes the importance of environmental factors in the onset of the disease. These include hygiene, exposure to bacterial endotoxins, living outdoors with contact with animals, air pollution, weather, and diet. Only a systematic study of all these elements can best illuminate the epidemiology of AD.
Keywords: Atopic dermatitis, environmental factors, illness, atmospheric pollution, the risk factor.